Relationship Executives Rewards With Financial Performance On Corporate Banking in Indonesia - Haninun HANINUN; Putri Cagora Nisa (Universitas Bandar Lampung (UBL), 2015)
The purpose of this research is to know the relationship of Executive rewards andfinancial performance on corporate banking in Indonesia. This research using a sample of as many as 140 28 banking company which is listed on the Indonesia stock exchange, whereas the observed financial reports for the past five consecutive years 2007 to 2011. Method of data collection was done manually inputted into the tabulated using excel. While the analysis used to determine the relationship of free variables (X) Executive Award (reward) and variable (Y), namely the financial performance is a non-parametric statistical analysis that tests rank correlation.The result of this research shows that by using the level of significance of 0.05 as a two- sided test then 2.5% and n = 140 obtained a table t = 1,977. Whereas t calculate for debt to equity as seen from the output though the data is 1,3001 (t count < t table) then based on this t-test concluded the Executive reward no relationship with financial performance. Likewise testing to return on investment and return on equity, show t 5,7884 and 6,63034 of count (t count > t table) then concluded the Executive reward is a relationship with the financial performance of the banking companies listed on the Indonesia stock exchange.